Alphaxalone Binds in Inner Transmembrane β+–α− Interfaces of α1β3γ2 γ-Aminobutyric Acid Type A Receptors. (February 2018) - Ziemba, Alexis M.; Szabo, Andrea; Pierce, David W.; Haburcak, Marian; Stern, Alex T.; Nourmahnad, Anahita; Halpin, Elizabeth S.; Forman, Stuart A.
Abstract : Background: Neurosteroids like alphaxalone are potent anxiolytics, anticonvulsants, amnestics, and sedative-hypnotics, with effects linked to enhancement of γ-aminobutyric acid type A (GABAA ) receptor gating in the central nervous system. Data locating neurosteroid binding sites on synaptic αβγ GABAA receptors are sparse and inconsistent. Some evidence points to outer transmembrane β + –α − interfacial pockets, near sites that bind the anesthetics etomidate and propofol. Other evidence suggests that steroids bind more intracellularly in β + –α − interfaces. Methods: The authors created 12 single-residue β3 cysteine mutations: β3T262C and β3T266C in β3-M2; and β3M283C, β3Y284C, β3M286C, β3G287C, β3F289C, β3V290C, β3F293C, β3L297C, β3E298C, and β3F301C in β3-M3 helices. The authors coexpressed α1 and γ2L with each mutant β3 subunit in Xenopus oocytes and electrophysiologically tested each mutant for covalent sulfhydryl modification by the water-soluble reagent para-chloromercuribenzenesulfonate. Then, the authors assessed whether receptor-bound alphaxalone, etomidate, or propofol blocked cysteine modification, implying steric hindrance. Results: Eleven mutant β3 subunits, when coexpressed with α1 and γ2L, formed functional channels that displayed varied sensitivities to the three anesthetics. Exposure to para-chloromercuribenzenesulfonate produced irreversible functional changes in ten mutant receptors. Protection by alphaxalone was observed in receptors with β3V290C, β3F293C, β3L297C, or β3F301C mutations. Both etomidate and propofol protected receptors with β3M286C or β3V290C mutations. Etomidate also protected β3F289C. In α1β3γ2L structural homology models, all these protected residues are located in transmembrane β + –α − interfaces. Conclusions: Alphaxalone binds in transmembrane β + –α − pockets of synaptic GABAA receptors that are adjacent and intracellular to sites for the potent anesthetics etomidate and propofol. Abstract : Alphaxalone contacts were identified in the inner transmembrane β + –α − intersubunit clefts of γ-aminobutyric acid type A (GABAA ) receptors. These sites are adjacent to the outer transmembrane sites where etomidate and propofol act. The results suggest that large portions of the transmembrane intersubunit clefts of GABAA receptors are allosterically coupled to ion channel gating. These clefts form a number of distinct binding sites for pharmacologic agents that include neurosteroids and currently used intravenous anesthetics.